2011
DOI: 10.3390/d4010001
|View full text |Cite
|
Sign up to set email alerts
|

Social Organization of Crop Genetic Diversity. The G × E × S Interaction Model

Abstract: A better knowledge of factors organizing crop genetic diversity in situ increases the efficiency of diversity analyses and conservation strategies, and requires collaboration between social and biological disciplines. Four areas of anthropology may contribute to our understanding of the impact of social factors on crop diversity: ethnobotany, cultural, cognitive and social anthropology. So far, most collaborative studies have been based on ethnobotanical methods, focusing on farmers’ individual motivations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
75
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 108 publications
(153 reference statements)
2
75
0
6
Order By: Relevance
“…The association between the race kafir and the Bantu agricultural tradition is a well-established theory (2,10,14,29,44). In this study, we found that 90% of the sorghums in the Southern population were from the Niger-Congo language family areas where Bantu languages are spoken, and 46% of them were classified as kafir.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between the race kafir and the Bantu agricultural tradition is a well-established theory (2,10,14,29,44). In this study, we found that 90% of the sorghums in the Southern population were from the Niger-Congo language family areas where Bantu languages are spoken, and 46% of them were classified as kafir.…”
Section: Resultsmentioning
confidence: 99%
“…operating at finer scales. On-farm management of crop varieties and cultural boundaries influencing the diffusion of seeds, practices, and knowledge are important local-scale explanatory factors behind patterns of regional and continental scale associations between ethnolinguistic groups and crop genetic structure (27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Neighborhood groups [9] and marriage exchanges are other social factors that shape crop diversity at local and regional levels [16][17][18][19].…”
mentioning
confidence: 99%
“…While ecological, cultural, and socioeconomic factors influence crop genetic diversity, few studies have examined the influence of cultural factors on the genetic diversity of globally minor crops [7,19]. Tartary buckwheat (Fagopyrum tataricum (L.) Gaertn.…”
mentioning
confidence: 99%
“…(2) evidenciar a capacidade protagonista dos agricultores e a efetividade do MGP -Modelo: genótipo x ambiente x social (Leclerc;d'Eeckenbrugge, 2012); (3) promover o uso e a conservação in situ on farm. O melhoramento participativo surgiu como uma alternativa aos programas conduzidos pelas instituições do setor formal de países em desenvolvimento.…”
Section: Contribuições Da Pesquisa Aos Pequenos Agricultoresunclassified